The organisational value of international assignments. - Renshaw, Phil St John (Cranfield University, 2019)
Our theoretical understanding and knowledge of the field of international assignments (IAs) has expanded enormously since Edström and Galbraith’s (1977) seminal paper evaluating the reasons that organisations use expatriation. In that time many underlying features and our understanding of the IA landscape have changed. This includes the reasons to use IAs, the recognition of and increasing use of more flexible IAs such as short-term and commuter assignments, as well as a move away from the traditional HQ-subsidiary IA. Despite this, academic knowledge regarding the value that is generated for organisations using IAs is unclear. More surprisingly perhaps, practitioner consultancy surveys of Global Mobility consistently report a desire to address this issue with relatively little success. Rather the practitioner field focuses on cost issues even though they are unable to place this in a value context. As a step to resolving this imbalance, this thesis contributes to understanding the organisational value of IAs through four interconnected studies written as journal articles. The context is first established using a systematic literature review (SLR) of the field. This is then built upon by a paper addressing the confusions regarding the definition of ‘organisational value’, applying and extending an existing framework using the IA construct. Together these provide a detailed understanding of the literature field emphasising a relational perspective, an extended model for understanding organisational value, and research propositions to move the field forward. The final two papers use empirical case study interviews in the public sector to demonstrate how two different theoretical lenses, the Dynamic Capabilities View and Real Options Theory respectively, extend our theoretical understanding of the underlying phenomenon. The over-riding contribution of this thesis is its explanation of the organisational value of IAs. This value arises through the positive impacts of IAs on the microfoundations of dynamic capabilities and hence their contribution to the long term competitiveness of the organisation. Furthermore, IAs are shown to be types of real option. This theoretical positioning adds significantly to the understanding of how IAs affect organisations and offers explanations for some of the issues in the IA literature such as the negative impact of high attrition. Furthermore, this thesis demonstrates that IA organisational value needs to be considered from the combined perspectives of the home (sending party) and the host (receiving party) whilst taking a relational view. In other words the relationships between the home and the host are affected by a wide range of factors all of which have the potential to change the value to each of these parties as well as the combined total value. These factors also extend to the relational context within which the home and host sit including the value implications for other parties within their intra- organisational system. This is a distinct change to extant research which empirically considers either the host (subsidiary) or the overall organisation when assessing the organisational value of IAs. From a practitioner perspective this bifurcation of the home and the host within their relational context creates significant consequences for the implementation of IAs, the HR practices managing them and the determination of the value they create.
Keywords: Expatriation; global mobility; dynamic capabilities; real options theory; real-options-reasoning; international assignments; public sector